Journey to Smart Bangladesh: Realities and Challenges - Ahmed, Tanji; Hasan, Nazmul; Akter, Runa (International Journal of Qualitative Research, 2023)
Bangladesh, a nation renowned for its resilience and quick growth, has started on a transformational path to become a "Smart Bangladesh." This vision entails utilizing technological advancements to enhance the lives of its citizens, improve governance, and foster sustainable economic growth. To identify the obstacles preventing the realization of a fully smart nation, this study evaluated the current technological landscape, governmental initiatives, and societal integration. Moreover, the study assessed policy gaps, infrastructure constraints, socioeconomic barriers, and citizen engagement. Therefore, the main purpose of the study was to comprehensively measure the trajectory towards a 'Smart Bangladesh.' The study was conducted using a qualitative approach, whereas secondary data were analyzed to reach its findings. The findings of the study revealed the paradigm shift from digital Bangladesh to smart Bangladesh, the development approaches of digital Bangladesh to smart Bangladesh, the diagnoses of transforming digital Bangladesh to smart Bangladesh, and the implications of smart technologies (IoT, AI, blockchain technology, big data analysis, etc.) in transforming digital Bangladesh to smart Bangladesh. Similarly, the study highlighted the challenges behind implementing smart Bangladesh. However, collaboration among the government, private sector, academic community, and civil society is essential for implementing smart Bangladesh. Additionally, it is essential to establish exhaustive policies, laws, and regulations to govern emerging technologies and protect citizen rights. Nevertheless, the findings of the study will provide both theoretical and practical contributions, especially in building the potential of technology to drive sustainable development, uplift communities, and shape a brighter future for all its citizens.